Anti-depression effectiveness of essential oil from the fruits of Zanthoxylum bungeanum maxim. on chronic unpredictable mild stress-induced depression behavior in mice - Tang, Dandan; Liang, Qi; Zhang, Mengmeng; Li, Meiyan; Zhang, Qing; Zhang, Siyuan; Ai, Li; Wu, Chunjie (Frontiers in Pharmacology, 2022)
The fruits of Zanthoxylum bungeanum Maxim. was a popular traditional Chinese herbal medicine for pain relief, itching prevention, and diarrhea relief. The fruits of Zanthoxylum bungeanum Maxim. essential oil (HEO) had an effect of improving anxiety and other emotional disorders. In this paper, we aim to systematically research the antidepressant effects of HEO on Chronic Mild Unpredictable Stimulation (CUMS) mice and explore the relevant molecular mechanisms. Experimental mice were exposed to CUMS for 8 weeks. Meanwhile, for 8 weeks, Sertraline hydrochloride (20 mg/kg/day) and HEO (50, 100, and 150 mg/kg/day) were administered by gavage. HEO treatment increased residence time of central zone in OFT and open-arm in EPM test but decreased immobility times in FST and TST. Moreover, HEO treatment improved the levels of 5-HT, DA, NE, and BDNF, but reduced CRF and CORT levels of the HPA axis in the hippocampus. Network pharmacology predicted the possible mechanisms for the antidepressant effects of HEO by regulation of PI3K/Akt signaling pathway. The mRNA expression of PI3K and Akt were increased, and immunofluorescence results in the hippocampus indicated that HEO treatment could increase the phosphorylation of PI3K and Akt. Besides, the viability of CORT-treated PC12 cells was significantly improved by HEO treatment. The AO-EB staining, MOMP analysis, and flow cytometry analysis results showed HEO inhibiting the CORT-induced apoptosis in PC12 cells significantly. Besides, the phosphorylation of PI3K and Akt in COTR-induced PC12 cells could increase by HEO treatment. In conclusion, HEO ameliorated depression behavior induced by CUMS, potentially via regulating HPA axis and activating PI3K/Akt signaling pathway to reduce neuronal apoptosis.